Distinct genomic organization, mRNA expression and cellular localization of members of two amastin sub-families present in Trypanosoma cruzi - Kangussu-Marcolino, Monica Mendes (2013)
Background: Amastins are surface glycoproteins (approximately 180 residues long) initially described in Trypanosoma cruzi as particularly abundant during the amastigote stage of this protozoan parasite. Subsequently, they have been found to be encoded by large gene families also present in the genomes of several species of Leishmania and in other Trypanosomatids. Although most amastin genes are organized in clusters associated with tuzin genes and are up-regulated in the intracellular stage of T. cruzi and Leishmania spp, distinct genomic organizations and mRNA expression patterns have also been reported.Results: Based on the analysis of the complete genome sequences of two T. cruzi strains, we identified a total of 14 copies of amastin genes in T. cruzi and showed that they belong to two of the four previously described amastin subfamilies. Whereas delta-amastin genes are organized in two or more clusters with alternating copies of tuzin genes, the two copies of beta-amastins are linked together in a distinct chromosome. Most T. cruzi amastins have similar surface localization as determined by confocal microscopy and western blot analyses. Transcript levels for delta-amastins were found to be up-regulated in amastigotes from several T. cruzi strains, except in the G strain, which is known to have low infection capacity. in contrast, in all strains analysed, beta-amastin transcripts are more abundant in epimastigotes, the stage found in the insect vector.Conclusions: Here we showed that not only the number and diversity of T. cruzi amastin genes is larger than what has been predicted, but also their mode of expression during the parasite life cycle is more complex. Although most T. cruzi amastins have a similar surface localization, only delta-amastin genes have their expression up-regulated in amastigotes. the results showing that a sub-group of this family is up-regulated in epimastigotes, suggest that, in addition of their role in intracellular amastigotes, T. cruzi amastins may also serve important functions during the insect stage of the parasite life cycle. Most importantly, evidence for their role as virulence factors was also unveiled from the data showing that delta-amastin expression is down regulated in a strain presenting low infection capacity.